2017
DOI: 10.1007/s12526-017-0715-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity of giant clams (Tridacna spp.) and their associated Symbiodinium in the central Red Sea

Abstract: Genetic diversity of giant clams (Tridacna spp.) and their associated Symbiodinium in the central Red Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 67 publications
(94 reference statements)
1
28
1
Order By: Relevance
“…DeBoer and collaborators [10] showed that giant clams that harbor Symbiodinium (formerly known as "clade A"), a typical temperature-and light-resistant algal genus in corals, are more sensitive to thermal and light stress than those that harbor Cladocopium. This result is, however, inconsistent with a recent report on tridacnids of the Red Sea, where Symbiodinium was found as the unique algal genus in clams that lived in high temperature and salinity conditions [16]. The role and potential flexibility of the Symbiodiniaceae assemblage of giant clams need clarification in order to better understand the threats and adaptive capacity of these important reef organisms.…”
Section: Introductioncontrasting
confidence: 87%
See 1 more Smart Citation
“…DeBoer and collaborators [10] showed that giant clams that harbor Symbiodinium (formerly known as "clade A"), a typical temperature-and light-resistant algal genus in corals, are more sensitive to thermal and light stress than those that harbor Cladocopium. This result is, however, inconsistent with a recent report on tridacnids of the Red Sea, where Symbiodinium was found as the unique algal genus in clams that lived in high temperature and salinity conditions [16]. The role and potential flexibility of the Symbiodiniaceae assemblage of giant clams need clarification in order to better understand the threats and adaptive capacity of these important reef organisms.…”
Section: Introductioncontrasting
confidence: 87%
“…While Tridacna crocea is predominantly associated with one algal genus at a time (Symbiodinium, Cladocopium, or, less frequently, Durusdinium), Tridacna squamosa and Tridacna maxima typically harbor multiple genera simultaneously [10,11], except in the Red Sea where they exclusively associate with Symbiodinium spp. [16]. This species-specific symbiosis with Symbiodiniaceae can be disrupted by environmental change that-similar to corals-can lead the expulsion or apoptosis of the photosynthetic symbionts [17][18][19][20] and cause clam bleaching and, subsequently, death.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of these associated algal symbionts might therefore also impact the susceptibility to (high) light levels, as different genera of Symbiodiniaceae (in symbiosis) exhibit different physiological and ecological patterns, including sensitivity to light and temperature (Rowan et al, 1997;Berkelmans and Van Oppen, 2006). However, a previous study on Red Sea giant clams and their associated Symbiodiniaceae (Pappas et al, 2017) reports that T. maxima in the region exclusively associated with Symbiodinium spp. (previously clade A), which was thus assumed to represent an optimal group for the local environmental conditions.…”
Section: Light-dependent Calcification and Production In Red Sea Gianmentioning
confidence: 99%
“…Giant clams on shallow reefs allow for the establishment of a diverse in-situ reservoir of interacting fungal, bacterial, and micro-algal communities (Baker 2003;Neo et al 2015 (Baillie et al 2000;DeBoer et al 2012;Ikeda et al 2017;Ikeda et al 2016;Pappas et al 2017;Trench et al 1981). Similar to coral symbiosis, it is assumed that the genotypic composition of Symbiodiniaceae in giant clams is influenced by environmental or physical parameters (e.g.…”
Section: Paving the Way For Comprehensive Biodiversity Assessment Of mentioning
confidence: 99%